Asymptomatic COVID-19 as a Risk Factor of Diabetic Ketoacidosis and Mucormycosis: A Case Report and Review of the Literature - Soheila Torabiyan; Behnam Dalfardi; Mojgan Sanjari (Case Reports in Endocrinology)
Mucormycosis is a lethal and life-threatening fungal infection. Several cases describing the association of COVID-19 and mucormycosis have been reported. In this article, we report a 58-year-old female with a history of diabetes mellitus type 2 who presented by diabetic ketoacidosis, rhino-orbital mucormycosis, and COVID-19. The patient was treated with liposomal amphotericin B and debridement of necrotic tissue of the rhino-orbital area and paranasal sinuses. Unfortunately, she passed away a few days after orbital surgery. We also conducted a review of the literature and reported 3 other similar cases that suffered from mucormycosis in association with COVID-19 and diabetic ketoacidosis and discussed the importance of this association.